اللسانيات الحاسوبية العربية : المفهوم والتطبيقات والجدوى - العناتي، وليد أحمد (جامعة الزرقاء - عمادة البحث العلمي, 2005)
يقصد هذا البحث إلى تبيان المفاهيم الرئيسة للسانيات الحاسوبية، كونها وجها من وجوه نمذجة اللغة وتمثيلها للحاسوب تحقيقا لغاية عظيمة؛ أن نهيئ للحاسوب كفاية لغوية تشبه ما يكون للإنسان حين ينتج اللغة ويستقبلها ثم يدركها ويفهمها. ولما كان الحاسوب الوسيلة الرئيسة في نشر أفكار العولمة لزمنا أن نتناول أهمية اللسانيات الحاسوبية في تهيئة اللغة العربية للمعالجة الآلية، ولمواجهة هيمنة الإنجليزية وطغيانها الجارف؛ فكان تعريب الحاسوب الإجراء الأمثل لتهيئة العربية لهذه المواجهة، ولإعدادها لدخول عصر المعرفة وبناء مجتمع معرفة عربي باللغة العربية. ينبه البحث إلى أهمية اللسانيات الحاسوبية العربية في الصراع الثقافي والعلمي والحضاري الذي تفرضه قوى العولمة والهيمنة. وكان من لوازم البحث الإشارة إلى وجوه استثمار اللسانيات الحاسوبية في خدمة اللغة العربية ودعمها في سياق الثورة المعلوماتية وتحدياتها الثقافية والحضارية والاقتصادية؛ تمهيدا لتوطين علوم المعلوماتية في البيئة العربية باللغة العربية. وانتهى البحث إلى تبيان أهمية اللغة العربية في بناء تكتل معلوماتي يحقق للعرب شيئا من التوازن التقني والعلمي في العالم. This paper aims at clarifying the concepts of Computational Linguistics as a means of modeling and representing language to a computer. This, in turn, aims at providing the computer with a form of linguistic competence that would enable it to produce, receive, become aware of, and understand language as a human being would. Due to the fact that computers are the main method of spreading the ideas of globalization, it has become necessary to discuss the importance of Computational Linguistics in preparing the Arabic language for mechanical processing, in order to face the fast moving dominance of the English language. Computer Arabization has been considered the best means of preparing the Arabic language for the age of knowledge and for its important role in building an Arab knowledge society. The paper also points out the important role of Arabic Computational Linguistics in facing the cultural and scientific conflict imposed by the dominating forces of globalization. It also refers to the use of Computational Linguistics in supporting the Arabic language as it faces the informational revolution and its cultural and economic challenges. Such aspects would be considered as a first step in establishing Arabic Information Technology that uses the Arabic language. In conclusion, the paper points out the importance of the Arabic language in building an Arab informational alliance that would establish some kind of scientific and technological balance in the world.
804616
Keywords: الصرف -- اللسانيات -- علماء اللغة -- اللغة العربية -- الحاسبات الإلكترونية -- النحو العربي -- المعاجم اللغوية -- العولمة -- اللغة العربية -- التعريب